From Diagnosis to Health Practice: Polycythemia Vera. A Literature Review - Siekaniec, Katarzyna; Roś, Bartosz; Kuchenbeker, Natalia; Dojs, Adriana; Mierzwińska-Mucha, Julia; Jakubowicz, Magdalena; Kowalewski, Wojciech (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Polycythemia vera (PV) is a chronic myeloproliferative neoplasm, part of the group of Philadelphia-negative neoplasms alongside essential thrombocythemia and myelofibrosis. It is characterized by elevated red blood cell mass, frequently accompanied by leukocytosis and thrombocytosis. A JAK2 mutation is present in about 95% of cases, typically with low erythropoietin levels. This study aims to review the current understanding of PV, including its pathophysiology, diagnostic criteria, treatment options, and emerging therapies. A brief description of the state of knowledge: PV is rare, with an incidence of 0.01–4 cases per 100,000 annually, and is usually diagnosed between the ages of 60 and 65. Symptoms stem from increased blood viscosity and include headaches, aquagenic pruritus, thrombosis, and splenomegaly. Diagnosis relies on elevated hemoglobin/hematocrit, bone marrow findings, and JAK2 mutation. According to ICC and WHO criteria, diagnosis can sometimes be made without bone marrow biopsy. Standard treatment includes low-dose aspirin and phlebotomy, with cytoreductive therapy (hydroxyurea or pegylated interferon) based on thrombotic risk. New drugs such as rusfertide, idasanutlin, and givinostat show promise in symptom control and potential disease modification. Summary: While current therapies effectively manage hematocrit and thrombotic risk, they do not address the root cause of PV. Novel treatments targeting molecular mechanisms may improve quality of life and reduce the risk of progression to myelofibrosis or acute leukemia. Further research is needed to develop curative strategies.